A new generic circumscription in tribe Lycieae (Solanaceae) - Levin, Rachel (2011)
Tribe Lycieae (Solanaceae) currently includes ca. 92 species in three genera. Two genera account for only a few species, as Phrodus is monotypic and Grabowskia includes just four species. By contrast, Lycium is one of the largest genera in the family, with ca. 88 species and over 95% of the species diversity in tribe Lycieae. Previous molecular studies have suggested that Lycium is paraphyletic and that species of Grabowskia are nested within Lycium. These studies also suggested that the genus Grabowskia was monophyletic, but questioned the integrity of species within it. Likewise, although the genus is defined by a unique fruit structure, morphology is of limited use in distinguishing species within Grabowskia. Depending on the study, Phrodus microphyllus has been placed either as sister to the rest of the tribe or nested within Lycium. In the present study we include data from two nuclear regions (granule-bound starch synthase and nitrate reductase) and four plastid spacer regions (trnH-pbsA, trnDGUC-trnT  GGU, rpl32-trnLUAG, ndhF-rpl32) to more clearly resolve evolutionary relationships among genera within the tribe and among species in Grabowskia. Results confirm that Lycium is paraphyletic and includes a monophyletic Grabowskia. However, inclusion of multiple accessions of several Grabowskia species does not support the maintenance of distinct species in the genus. In addition, Phrodus microphyllus is moderately supported as basal within the tribe. Given these results, which are further strengthened by morphological and cytological data, we synonymize three Grabowskia species with Grabowskia boerhaviifolia and include this species within Lycium, using its basionym, Lycium boerhaviifolium L.f. Additionally, we transfer Phrodus microphyllus to the genus Lycium, proposing a new combination: Lycium bridgesii (Miers) Levin, Miller & Bernardello. Tribe Lycieae is now monotypic, including the single genus Lycium.